1996
DOI: 10.1002/(sici)1097-0231(199610)10:13<1591::aid-rcm715>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ammonium Salt and Matrix in the Detection of DNA by Matrix-assisted Laser Desorption/Ionization Time-of-flight Mass Spectrometry

Abstract: The effect of ammonium salt in the detection of oligonucleotides by matrix-assisted laser desorptionlionization time-of-flight mass spectrometry has been systematically investigated using several matrices with ammonium salt additives. The results show that the presence of ammonium salt in the matrix has a beneficial effect on protonation and deprotonation of oligonucleotides in addition to suppressing alkali-ion adducts. These observations indicate that a good matrix for DNA detection could be made from two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 0 publications
2
48
0
Order By: Relevance
“…All matrices and additives, including 3-hydroxypicolinic acid (HPA) [31], 2,4,6-trihydroxyacetophenone (THAP) [32], anthranilic acid (AA) [33], 6-aza-2-thiothymine (ATT) [34], diammonium hydrogencitrate [35,36,37], and formic acid were purchased from Sigma (St Louis, MO, USA) or Aldrich Chemical (Milwaukee, WI, USA). External mass calibration was performed with a buckminsterfullerene mixture (C 60 with 10% C 70 ), also purchased form Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…All matrices and additives, including 3-hydroxypicolinic acid (HPA) [31], 2,4,6-trihydroxyacetophenone (THAP) [32], anthranilic acid (AA) [33], 6-aza-2-thiothymine (ATT) [34], diammonium hydrogencitrate [35,36,37], and formic acid were purchased from Sigma (St Louis, MO, USA) or Aldrich Chemical (Milwaukee, WI, USA). External mass calibration was performed with a buckminsterfullerene mixture (C 60 with 10% C 70 ), also purchased form Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we elaborated conditions for complex formation in volatile salt solutions known to be compatible with MALDI, e.g. ammonium salts which have been described as buffers and MALDI-matrix additives by several authors (25,29,41,42). Our final choice was 12.5 mM ammonium acetate in ultra-pure water, pH 7.…”
Section: Formation Of Complexes In a Buffermentioning
confidence: 99%
“…Use of these stable homodeoxythymidine signal molecules also allowed for the use of ␣CHCA as the MALDI matrix, which cannot be used for the analysis of oligonucleotides containing mixed nucleotide sequences because of substantial backbone fragmentation of these oligonucleotides in this matrix (33). Use of ␣CHCA is advantageous because this matrix forms a more confluent, easily sampled, ''lawn'' of crystals on the MALDI probe tip than other MALDI matrices commonly used for DNA analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Initial experiments (data not shown) showed that significant amounts of uncleaved probes are immobilized on the streptavidin-coated beads, eluted, and spotted on the MALDI probe tip along with the signal molecules. The presence of these longer probes in the MALDI-TOF MS analysis was a potential concern because of the fragmentation propensity of these oligonucleotides when ␣CHCA is used as the matrix (33). The resultant fragment ions could have m͞z values similar to those of the signal molecules produced in the secondary Invader reaction, leading to increased background levels and possibly yielding false-positive results.…”
Section: Discussionmentioning
confidence: 99%